2018
DOI: 10.1159/000495299
|View full text |Cite
|
Sign up to set email alerts
|

Intra-Plaque Vessels on Contrast-Enhanced Ultrasound Sonography Predict Carotid Plaque Histology

Abstract: Background and Purpose: Although the echogenicity of carotid plaques on carotid enhanced ultrasound (CEUS) was reported to correlate with the historological density of intra-plaque neovessels, it is unclear whether the intra-plaque vessel size is associated with carotid plaque vulnerability. We evaluated the relationship of size of intra-plaque vessels on CEUS with carotid plaque histology. Methods: We prospectively registered patients with carotid stenosis who were hospitalized to receive carotid endarterecto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…However, it is difficult to detect intraplaque neo-capillaries with conventional B-mode, color Doppler, or even power Doppler. Several studies (Huang et al, 2016; Amamoto et al, 2019) showed that CEUS had a high sensitivity in detecting neo-capillaries in carotid plaques. Based on a meta-analysis, the measurement of the degree of neovascularization was a promising tool in plaque evaluation (Huang et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…However, it is difficult to detect intraplaque neo-capillaries with conventional B-mode, color Doppler, or even power Doppler. Several studies (Huang et al, 2016; Amamoto et al, 2019) showed that CEUS had a high sensitivity in detecting neo-capillaries in carotid plaques. Based on a meta-analysis, the measurement of the degree of neovascularization was a promising tool in plaque evaluation (Huang et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…However, the definition of histological vulnerability varied among studies and may have contributed to the heterogeneity in outcomes. A study defined vulnerability as a combination of large lipid core, increased inflammatory cell presence, and a lack of smooth muscle cells [ 82 ] whereas other studies used the American Heart Association (AHA) classification of atherosclerotic plaque [ 83 , 84 ].…”
Section: Contrast-enhanced Ultrasound (Ceus)mentioning
confidence: 99%
“…(1) Plaque rupture or ulceration (discontinuous fibrous cap, pulsation with the heart beat, or a "volcanic crater" sign); (2) large lipid core or hemorrhage in the plaque (hypoechoic or echolucent characteristics) [7,8]; (3) contrast-enhanced ultrasound or superb microvascular imaging show that the dynamic moving hyperechoic light points extend from the adventitia to the inside of the plaque, indicating neovascularization in the plaque [9].…”
Section: Ultrasonic Characteristics Of Vulnerable Plaquesmentioning
confidence: 99%